Decoupling Control Strategy of D-STATCOM - Guangzheng Wang; Zeng Ping; Juan Zhang; Yujie Guo (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In Distribution Network, Distribution Static Synchronous Compensator (D-STATCOM) can stabilize turn-on point voltage, effectively reduce the transmission losses in power, improve the power factor and prevent the non-linear load. But under the circumstance of the d- and q-axis, D-STATCOM is a non-linear and strong coupling system, so decoupling control is very useful, that is because the decoupling control can ensure the output current fast track and have on different with the setting values. Study the decoupling control strategy of D-STATCOM, through the analysis of its basic structure, and then get the model of the coupling term. Due to avoid active and reactive current coupling, Fuzzy Immune PI Controller and inverse system method are combined to be used in the original system. Finally, the results are shown by the MATLAB simulation that the proposed decoupling control strategy is very good, because the performance is excellent, the structure is simple and easy to be implemented. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2684